2020
DOI: 10.3390/ijms21239304
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Shielding Enhances Radiation Resistance by Promoting DNA Repair Process in Human Bronchial Epithelial Cells

Abstract: With the advent of long-duration space explorations, ionizing radiation (IR) may pose a constant threat to astronauts without the protection of Earth’s magnetic field, or hypomagnetic field (HMF). However, the potential biological effects of a HMF on the cellular response to IR have not been well characterized so far. In this study, immortalized human bronchial epithelial cells were exposed to X-rays under either a geomagnetic field (GMF, ~50 uT) or HMF (<50 nT) culture condition. A significant increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…A recent in vitro study found that the glucose consumption and mitochondrial membrane potential of HMF-exposed skeletal muscle cells were significantly lower than those of the geomagnetic control ( Fu et al, 2016 ); the level of intracellular genotoxic substance—reactive oxygen species (ROS)—was repressed in HMF-cultured human neuroblastoma cells ( Zhang et al, 2017 ). In accordance with these findings, our recent study indicated that HMF simulated by geomagnetic shielding enhances radiation resistance by elevating the capacity of genomic stability maintenance in human bronchial epithelial cells ( Xue et al, 2020 ). On the other hand, HMF has been reported to increase the lipid peroxide oxidation in the lung, liver, kidney, and small intestine of guinea pigs and mice after a short exposure in a shielded chamber ( Babych, 1995 , 1996 ).…”
Section: Hmf Effect On Metabolism Embryonic Development and Neural supporting
confidence: 75%
“…A recent in vitro study found that the glucose consumption and mitochondrial membrane potential of HMF-exposed skeletal muscle cells were significantly lower than those of the geomagnetic control ( Fu et al, 2016 ); the level of intracellular genotoxic substance—reactive oxygen species (ROS)—was repressed in HMF-cultured human neuroblastoma cells ( Zhang et al, 2017 ). In accordance with these findings, our recent study indicated that HMF simulated by geomagnetic shielding enhances radiation resistance by elevating the capacity of genomic stability maintenance in human bronchial epithelial cells ( Xue et al, 2020 ). On the other hand, HMF has been reported to increase the lipid peroxide oxidation in the lung, liver, kidney, and small intestine of guinea pigs and mice after a short exposure in a shielded chamber ( Babych, 1995 , 1996 ).…”
Section: Hmf Effect On Metabolism Embryonic Development and Neural supporting
confidence: 75%
“…In the deep space environment, astronauts will be more susceptible to space radiation-induced adverse effects after leaving the protection of the earth’s magnetic field, which highlights the importance of the combined biological effect study of hypomagnetic field and space radiation. By studying DNA damage and repair of immortalized human bronchial epithelial BEAS-2B cells exposed to HMF (<50 nT) after 2 Gy X-ray irradiation, Xue et al (2020) found increased survival, less DNA damage and more efficient DNA damage repair, suggesting potential application of HMF in radiation protection. This was also the first that identified that HMF participates in the process of DNA damage repair induced by irradiation.…”
Section: Combined Biological Effects Of Space Environmental Factors I...mentioning
confidence: 95%
“…Therefore, the results obtained here inspire future studies in a field situation, together with contributing a new physico-chemical approach to understanding several biological features, as seen in the recent literature. [66][67][68][69][70][71] In short, the results obtained in this study indicate the potential of homeopathic potencies to mitigate environmental problems related to microorganisms that impact ecosystems. This would contribute toward the FAO's recommendation for a "One Health" approach 55,56 and the sustainable development goals for the coming decades.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the results obtained here inspire future studies in a field situation, together with contributing a new physico-chemical approach to understanding several biological features, as seen in the recent literature. 66 67 68 69 70 71…”
Section: Discussionmentioning
confidence: 99%